Factors affecting hotel visitors' usage of guest empowerment technology (GET) - Lai, Hang Kwan; Siew, Jing Chia; Rickson Khor; Teck, Hou Wong; Yuan, Xu Lin; Chen, Xi Zhao (IGI Global, 2016)
The aim of this study is to determine the factors affecting the usage of Guest Empowerment Technologies (GET) in hotels among hotel visitors in Labuan, Malaysia. The research used multiple regression for data analysis across a sample of 225 respondents who stayed in hotel at least once in a year. Their participation was voluntarily. Results confirmed that the core factor affecting users' intention to use of GET is perceived usefulness. Meanwhile, all variables are proven to be significant to each other and perceived usefulness had the strongest influencing on the users' intention to use of GET. The findings provide additional information to the hotels for further understanding their consumers' characteristics in hotels. Having this information, the proposed framework can be use as the basis for further research.